AB0266 Responsiveness and minimal important difference of the rheumatoid arthritis-work instability scale (ra-wis). (23rd January 2014) - Revicki, D.; Cifaldi, M. A.; Safikhani, S.; Chen, N.; Ganguli, A.
Abstract : Background: Within 2 to 3 years of disease, approximately 20 to 30% of patients with early rheumatoid arthritis (RA) become permanently work disabled (Allaire, 2008). Disability-associated 'work instability' defined as the mismatch between their functional capabilities and job demands, is a risk factor for loss of employment. The RA-WIS was developed to assess the level of risk for work disability in RA patients; however there is limited information on its responsiveness and minimal important difference (MID). Objectives: The objective of this study was to evaluate the responsiveness and MID of the RA-WIS in patients with early RA. Methods: A secondary analysis was conducted using data from PROWD study, a 56-week, randomized, and controlled trial of patients with early RA (Bejarano, 2008). Clinical measures included American College of Rheumatology (ACR) response and Disease Activity Score-28 (DAS28), and patient-reported outcomes included the RA-WIS and Health Assessment Questionnaire Disability Index (HAQ-DI), which were collected at Baseline and at Weeks 12, 16, 24 and 56. Responsiveness of the RA-WIS was evaluated at Weeks 24 and 56 based on DAS28 (<3.2 vs. >3.2) and ACR response criteria (<20% vs. 20% to <50%;) using analysis of covariance, adjusting for age, gender and baseline RA-WIS scores. MID estimates were derived from these analyses. Results: A total of 148 patients were included in the analysis sample, and was 56% female, with a mean age of 46.8 years. Patients experienced RA symptoms for a mean 8.7 months with mean DAS scores of 5.9 and mean HAQ-DI scores of 1.3. Mean Baseline to Week 24 RA-WIS Total change scores were significantly different among ACR responder groups ( P ≤0.0001) and between DAS28 remission status groups ( P <0.001). There was a -5.3 to -7.7 point RA-WIS score change associated with an improvement of 20% to <50% in ACR from baseline to 24 or 56 weeks. There was a -5.4 to -6.1 point RA-WIS point change associated with a moderate response for DAS28 at 24 or 56 weeks. Conclusions: These findings provide evidence on the responsiveness of the RA-WIS for evaluating work disability in RA patients. The MID for the RA-WIS is estimated at 5 to 7 points. Disclosure of Interest: D. Revicki Consultant for: AbbVie, M. Cifaldi Shareholder of: AbbVie, Employee of: AbbVie. The design, study conduct, and financial support for the study/trial was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract., S. Safikhani Consultant for: AbbVie, N. Chen Shareholder of: AbbVie, Employee of: AbbVie. The design, study conduct, and financial support for the study/trial was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract., A. Ganguli Shareholder of: AbbVie, Employee of: AbbVie. The design, study conduct, and financial support for the study/trial was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract.